Electrospun One Dimensional (1D) Pseudocapacitive nanorods embedded carbon nanofiber as positrode and graphene wrapped carbon nanofiber as negatrode for enhanced electrochemical energy storage. (February 2022) - Selvaraj, Aravindha Raja; Raja, Iruthayapandi Selestin; Chinnadurai, Deviprasath; Rajendiran, Rajmohan; Cho, Inho; Han, Dong‐Wook; Prabakar, Kandasamy
Highlights: Pseudocapacitive α-MnO2 nanorods embedded CNF by electrospinning technique. Highly conductive rGO wrapped CNF acted as a negatrode. The CNF/MnO2 exhibited high specific capacitance of 271 Fg −1 . The CNF/rGO//CNF/MnO2 device delivered a specific energy of 34 Wh Kg −1 at 192 W kg −1 . Abstract: A simple and low-cost fabrication of high-performance supercapacitors is an excellent choice for the future energy storage device. In view of this, we have synthesized carbon nanofibers (CNF) from polyacrylonitrile without using activating or templating agent by an electrospinning process. The reduced graphene oxide (rGO) sheets and manganese dioxide (MnO2 ) nanorods prepared separately are added to CNF in order to enhance the capacitance and stability of the CNF electrodes depending on the polarity of the electrode material. The MnO2 nanorods embedded carbon nanofibers (CNF/MnO2 ) supercapacitors performances have been maximized by an electrospinning process. The unique porous CNFs have not only improved the contact area between the electrode and the electrolyte, but also improve the intrinsic conductivity of MnO2 during the electrochemical tests. The CNF/MnO2 nanocomposite shows a high specific capacitance of 271.4Fg −1 due to the pseudo-capacitance effect from MnO2 and high surface area from CNF network. Moreover, the conductivity and high surface area tuned hierarchically structured rGO with CNFs (rGO/CNF) as a negative electrode resulted in higher specific capacitance of 251.5 Fg −1 at 0.5 A g −1 . A symmetric supercapacitor device fabricated from CNF/MnO2 electrode shows energy and power density of 17.3 W h kg −1 and 122.9 kW kg −1 respectively. We further assembled asymmetric supercapacitor with a rGO/CNF as negatrode and MnO2 /CNF as positrode which shows an increased potential window of 2 V and high energy density of 34.4 W h kg −1 at a power density of 192 kW kg −1 .